“Eco School Project” Program to Create an Environmentally Friendly School Garden at UPTD SDN Cinini Sumbermulya Village Indramayu - Yusrina Nafilah; Idah Hamidah; Eva Yuliana (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
Climate change and environmental degradation are increasingly urgent global issues to address. Global warming, air pollution, deforestation, and various other forms of environmental damage threaten the sustainability of life on earth. In facing these challenges, education plays a key role in shaping pro-environmental awareness and behavior among the younger generation. Schools as educational institutions have a great responsibility in instilling environmental values ​​in students. One relevant initiative in the context of environmental education is the "Eco School Project." This program aims to create an environmentally friendly school garden, which not only functions as a green space, but also as a means of education for students. Through this program, students are invited to be directly involved in environmental conservation efforts, so that they can understand the importance of preserving nature and implementing environmentally friendly behavior in everyday life. To maintain environmental sustainability, wise management must be carried out. This condition requires an increase in environmental awareness among the community, especially the younger generation. The "Eco School Project" is expected to be an effective environmental education model that can be implemented in various schools throughout Indonesia. On the other hand, schools often lack adequate green space, even though the presence of parks or gardens in the school environment has many benefits. School gardens can function as living laboratories for students to learn about ecosystems, plant life cycles, and the importance of water and soil conservation. In addition, the presence of green space in schools can also improve air quality, reduce air temperatures around the school, and create a healthier and more enjoyable learning environment. Realizing an environmentally friendly school garden through the "Eco School Project" requires collaboration between the school, students, parents, and the surrounding community. The involvement of these various parties not only increases the sense of ownership of the program, but also ensures the sustainability and success of this initiative. Support from the government and various environmental organizations is also very important in providing the necessary resources and technical guidance. As part of the program implementation, schools can hold various activities such as tree planting, creating organic gardens, 3R-based waste management (Reduce, Reuse, Recycle), and installing rainwater treatment systems. These activities not only provide practical experience to students, but also create a real positive impact on the school environment. Overall, the "Eco School Project" is a strategic step in increasing awareness and pro-environmental behavior among students. Through this program, it is hoped that a generation can be created that is more concerned and responsible for environmental sustainability, so that a greener and more sustainable future for the earth can be realized.